Tradisi Penguburan Ari-Ari di Masyarakat Kampung Jujuluk Dan Kaitannya Dengan Interaksi Sosial di Masa Kini - Andini Dwi Rizkyawati (Faculty of Social, Politic, and Law Science, Universitas Serang Raya, 2023)
Local wisdom is a way of life or a life strategy that refers to various cultures that have developed in a society with the aim of increasing prosperity and peace and harmony in society. Local wisdom itself will differ in each region depending on the culture of the people. In this modern era, Indonesian people have experienced many developments in their lives because of globalization and modernization. Many cultures have eroded over time because of modernization and globalization. Even so, there are still many cultures that still apply in every region in Indonesia. One tradition that still survives in Jujuluk Village, Rangkasbitung, Banten itself is the burial of the baby's placenta or placenta. Therefore, this study aims to identify what is meant by burial of the placenta for the people of Jujuluk Village, Rangkasbitung and how it relates to social interactions that occur in society. This study used a qualitative approach with data collection methods in the form of in-depth interviews with 2 informants. The results of this study indicate that there are several links that exist between the tradition of burial of the placenta and the social interactions that occur in the surrounding community.